Association of vitamin D receptor gene polymorphism with type 1 diabetes mellitus risk in children: A protocol for systematic review and meta-analysis. Issue 28 (16th July 2021) - Ran, Yalin; Hu, Suyuan; Yu, Xiaohua; Li, Renjun
Abstract: Background: Recent genetic association studies showed that there are contradictory results on the relationship between vitamin D receptor (VDR) gene polymorphisms and type 1 diabetes mellitus (T1DM) risk in children. The purpose of this systematic review is to collect the currently available evidence to evaluate the relationship between VDR gene polymorphisms and the risk of T1DM in children. Methods: Such medical databases as Wanfang Data, Chinese Biomedical Literature Database, Chinese National Knowledge Infrastructure, Chongqing VIP Chinese Science and Technology Periodical Database, PubMed, Embase, and Web of Science were extensively searched for relevant literatures published before June 2021 with the focus on the relationship between VDR gene polymorphisms and the risk of T1DM in children. The risk of bias was evaluated as per the Newcastle-Ottawa Scale by 2 independent researchers. Meta-analysis was performed to quantify the relationship between VDR gene polymorphisms and T1DM risk in children. Results: The results of this meta-analysis would be submitted to a peer-reviewed journal for publication. Conclusion: The relationship between VDR gene polymorphisms and T1DM risk in children is explored via this meta-analysis. Ethics and dissemination: Ethical approval was not required for this study. The systematic review will be published in a peer-reviewed journal, presented at conferences, and shared on social media platforms. Osf Registration Number: DOI 10.17605/OSF.IO/Q8XA5.